Spiritual theology : a systematic study of the Christian life - Chan, Simon (Downers Grove, Ill. : InterVarsity Press, 1998)
Spiritual Theology is a rare book, surveying the little-explored landscape where systematic theology and godly praxis meet, highlighting the connections between Christian doctrine and Christian living. It draws out the spiritual implications of particular aspects of systematic theology, allowing formulas to drop into the background and bringing the mystery of the faith to the fore. Spiritual Theology achieves all of this while remaining unabashedly evangelical and truly ecumenical. It is firmly grounded in the sources of the Protestant, Catholic and Orthodox traditions, well abreast of contemporary theological currents and crossculturally conversant from an Asian perspective.
Pt. 1. The Theological Principles of Spiritual Theology. 1. Christian Spiritual Theology: Its Nature & Criteria. 2. The Christian Doctrine of God as the Foundation of Christian Spirituality. 3. Sin & Human Nature. 4. Salvation & the Life of Spiritual Progress. 5. The Church as the Community of Saints -- Pt. 2. The Practice of the Spiritual Life. 6. The Theology & Life of Prayer. 7. Spiritual Exercises Focusing on God & Self. 8. Spiritual Exercises Focusing on the Word. 9. Spiritual Exercises Focusing on the World. 10. The Rule of Life. 11. The Discernment of Spirits. 12. The Art of Spiritual Direction.
Includes bibliographical references (p. [285]-288) and indexes.
Keywords: Christian life; Spirituality